2019
DOI: 10.1016/j.heliyon.2019.e01142
|View full text |Cite
|
Sign up to set email alerts
|

Water transport properties of boron nitride nanosheets mixed matrix membranes for humic acid removal

Abstract: Ultrafiltration grade polysulfone-based mixed matrix membranes (MMMs) incorporated with two-dimensional boron nitride nanosheet (BNNS) was prepared via phase inversion method. The amount of BN incorporated was varied and the influence on membrane morphology, contact angle, surface charge, as well as water permeability and humic acid rejection were investigated. Results revealed that the addition of BN to the membrane matrix resulted in profound increase in water permeability (almost tripled to that of neat PSf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Obtained XRD patterns reveal peaks positioned at 2θ ~ 26.70°, 41.69°, 43.91°, and 50.13°. Main characteristic pattern located at 26.70 was readily indexed as 002 plane, while other diffraction peaks were indexed as 100, 101, and 102 planes, respectively, which correlate strongly with JCPDS reference # 00-034-0421 (Yuan et al 2017;Tang et al 2019). Significant peak was observed at 26.70° that relates to h-BN, while the interplanar spacing (d 002 ) evaluated through Bragg's law (nλ = 2dsinθ) was 0.339 nm (Huang et al 2013b).…”
Section: Resultssupporting
confidence: 54%
“…Obtained XRD patterns reveal peaks positioned at 2θ ~ 26.70°, 41.69°, 43.91°, and 50.13°. Main characteristic pattern located at 26.70 was readily indexed as 002 plane, while other diffraction peaks were indexed as 100, 101, and 102 planes, respectively, which correlate strongly with JCPDS reference # 00-034-0421 (Yuan et al 2017;Tang et al 2019). Significant peak was observed at 26.70° that relates to h-BN, while the interplanar spacing (d 002 ) evaluated through Bragg's law (nλ = 2dsinθ) was 0.339 nm (Huang et al 2013b).…”
Section: Resultssupporting
confidence: 54%
“…Hexagonal boron nitride ( h -BN) is a 2-D form of BN which is structurally analogous to graphene. It has received increasing attention because of its potential use in fields such as novel drug delivery systems, , energy applications, nanocomposites, and pollutant removal. , Common to all of these applications is the presence of the interface between the h -BN surface and organic or biological molecules, often in an aqueous environment. Enhancement in our understanding of the interaction strengths between these biomolecular species and h -BN at the interface, and the adsorbed structures of these biomolecules at the aqueous h -BN interface, will provide critical new insights to enable the rational design of new materials and optimize the processes involved …”
Section: Introductionmentioning
confidence: 99%
“…Tang et al 119 proposed the mixed matrix membrane fabrication regarding the BN impact, which showed an improvement in UF membrane performance, including high water permeability and humic acid rejection thanks to the negative surface charge and pore size increment. They prepared the casting solutions containing polysulfone (PSf) 120 could be noteworthy since they aimed to improve the wettability and antifouling.…”
Section: Phase Inversion Mixed Matrixmentioning
confidence: 99%
“…The fouling resistance parameter calculations showed a significant improvement in the reversible fouling ratio of the membrane. In the study conducted by Tang et al, 119 two-dimensional BN and PSf UF membranes were produced by the phase inversion method. It was revealed that the water permeability increased 3 times and caused a significant increase in humic acid rejection because of the enhancement in negative surface charge and pore size.…”
Section: 3mentioning
confidence: 99%